TNF-α-mediated downregulation of CD36 and phagocytic impairment of alveolar macrophages via upregulation of ADAM17 in asthma - Liu, Xingyue; Li, Ya; Shang, Feifei; Niu, Minzhu; Yan, Jiaqi; Xie, Minyu; Tao, Xiangnan; Huang, Han; Wu, Wenwen; Dong, Shu; Chen, Yingzi; Wu, Fan; et al. (Frontiers in Immunology, 2025)
BackgroundAlveolar macrophages (AMs) are specialized phagocytes in the airways that play a crucial role in maintaining bronchoalveolar homeostasis through phagocytosis, the clearance of apoptotic cells. However, the characteristics and molecular mechanisms of AMs-mediated phagocytosis during the pathogenesis of asthma remain poorly characterized.MethodsAn ovalbumin (OVA)-induced asthma model was established in mice through intraperitoneal sensitization followed by intranasal challenge. AMs were isolated from the bronchoalveolar lavage fluid of control and OVA-induced mice using adherence-based purification. The phagocytic capacity of AMs, as well as the expression levels of CD36 and ADAM17, were quantified by flow cytometry.ResultsA significant reduction in both phagocytic efficiency and CD36 expression was found in the AMs of OVA-induced mice compared to control mice. Blockade of CD36 resulted in a marked decline in the phagocytic efficiency of normal AMs. Expression of ADAM17 was found to be notably elevated on the surface of AMs from OVA-induced mice compared to controls. Knockdown of ADAM17 led to a substantial increase in CD36 expression and a corresponding increase in phagocytic efficiency. Stimulation with tumor necrosis factor-α (TNF-α) resulted in a significant upregulation in ADAM17 and marked downregulation in CD36 expression levels, as well as impaired the phagocytic efficiency of AMs. Importantly, ADAM17 knockdown attenuated the TNF-α-mediated downregulation of CD36 expression and the associated impairment of phagocytic capacity in AMs.ConclusionAMs from OVA-induced mice displayed significantly impaired phagocytic capacity. Airway TNF-α upregulated ADAM17, which in turn downregulated CD36 expression on AMs, ultimately suppressing their phagocytic function.